Hard rock hydraulics an introduction to modeling - Franciss, F. O. (Boca Raton : CRC Press, 2021)
Hard rock hydraulics concerns arrangements of adjoining intact rock blocks, occurring down to a depth of hundreds of meters, where groundwater percolates within the gaps between these blocks. During the last decades, technical papers related to successful or failed attempts for mining groundwater from hard rocks, and achievements or failures of public or mining developments with respect to these rocks, increased the knowledge of their hydraulics. Examples of activities where the mechanical behavior of these rocks highly interacts with their hydraulics are projects under the sea or groundwater level, such as open pits or underground mines, galleries, tunnels, shafts, underground hydropower plants, oil and LPG storage caverns, and deep disposal of hazardous waste. This book dedicated to hard rock hydraulics assumes some prior knowledge of hydraulics, geology, hydrogeology, and soil and rock mechanics. Chapter I discusses the main issues of modeling; chapter II covers the fundamentals of hard rock hydraulics; chapter III presents concepts regarding approximate solutions; chapter IV discusses data analysis for groundwater modeling; chapter V focuses on finite differences and chapter VI provides examples of some particular unusual applications. This book will help civil and mining engineers and also geologists to solve their practical problems in hydrogeology and public or mining projects.
OCLC-licensed vendor bibliographic record.
Keywords: Hydrogeological modeling; Hard rock mines and mining; TECHNOLOGY / Mining; TECHNOLOGY / Petroleum